2020
DOI: 10.5194/acp-20-1887-2020
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increase in reactive volatile organic compound (VOC) emissions from ships at berth after implementing the fuel switch policy in the Pearl River Delta Emission Control Area

Abstract: Abstract. Limiting fuel sulfur content (FSC) is a widely adopted approach for reducing ship emissions of sulfur dioxide (SO2) and particulate matter (PM), particularly in emission control areas (ECAs), but its impact on the emissions of volatile organic compounds (VOCs) is still not well understood. In this study, emissions from ships at berth in Guangzhou, southern China, were characterized before and after the implementation of the fuel switch policy (IFSP) with an FSC limit of 0.5 % in the Pearl River Delta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…PNC pl values attained in this work are similar to the concentrations of plumes observed in similar studies: median PNC values of 700 and 1470 cm −3 were measured during winter and summertime in southern Sweden, respectively (Ausmeel et al, 2019). A noticeably higher PNC concentration (2100 cm −3 ) of ship plumes was measured with airborne measurements right over the shipping lane in the southern Baltic Sea by Zanatta et al (2020) during the 0.10 m/m% FSC restriction. Concentrations observed by Zanatta et al (2020) were likely higher due to the fresher plumes (plume age ∼ 200-800 s).…”
Section: Particle Number Concentrations Of Exhaust Plumessupporting
confidence: 89%
See 4 more Smart Citations
“…PNC pl values attained in this work are similar to the concentrations of plumes observed in similar studies: median PNC values of 700 and 1470 cm −3 were measured during winter and summertime in southern Sweden, respectively (Ausmeel et al, 2019). A noticeably higher PNC concentration (2100 cm −3 ) of ship plumes was measured with airborne measurements right over the shipping lane in the southern Baltic Sea by Zanatta et al (2020) during the 0.10 m/m% FSC restriction. Concentrations observed by Zanatta et al (2020) were likely higher due to the fresher plumes (plume age ∼ 200-800 s).…”
Section: Particle Number Concentrations Of Exhaust Plumessupporting
confidence: 89%
“…This variation in the GMD from a minimum of 36, 39, and 31 nm to a maximum of 58, 55, and 51 nm for the FSC restrictions of 1.50 m/m%, 1.00 m/m%, and 0.10 m/m%, respectively, implies that particles either grow significantly or small particles evaporate when they are transported in the atmosphere. Zanatta et al (2020) found a similar behavior: increasing particle size as the age of the plumes increased. The atmospheric processing of plume particles is discussed more in Sect.…”
Section: Particle Number Size Distribution Of the Exhaust Plumesmentioning
confidence: 59%
See 3 more Smart Citations